Case Report: First case of percutaneous transhepatic cholangioscopy guided triple bridge drainage between multiple bile ducts for malignant hilar biliary obstruction - Tang, Gang; Zhang, Jie; Chen, Rui; Zhang, Jingyi; Zhou, Rongxing (Frontiers in Oncology, 2025)
BackgroundBiliary drainage for advanced malignant hilar biliary obstruction (MHBO) remains a significant challenge in current clinical practice.Case descriptionA 58-year-old male diagnosed with unresectable advanced intrahepatic cholangiocarcinoma with hilar obstruction and required palliative biliary drainage. Imaging revealed obstruction of the common bile duct, left hepatic duct, right anterior hepatic duct, and right posterior hepatic duct (Bismuth–Corlette type IV). Due to the failure of ERCP, we decided to bridge biliary drainage with percutaneous transhepatic cholangioscopy (PTCS) after multidisciplinary discussion. First, one-step PTCS was used to establish a channel between the skin and the right anterior hepatic duct. Then a puncture needle was used to puncture the right anterior hepatic duct to the distal common bile duct, and the first stent was inserted for bridging. Next, a puncture needle was used from the right anterior hepatic duct to the left hepatic duct and a second stent was inserted for bridging. Finally, a puncture needle was used to puncture the right anterior hepatic duct to the right posterior hepatic duct, and a third stent was inserted for bridging. Intraoperative X-ray examination with contrast agent injected through the sinus confirmed successful bridging. The jaundice disappeared a few days after surgery, and no post-procedure-related adverse events occurred.ConclusionThis case demonstrates that ultrasound-guided PTCS triple-bridge biliary drainage connecting multiple bile ducts is a feasible palliative option for MHBO and warrants further clinical investigation.